Re-reading the salaryman in Japan : crafting masculinities - Dasgupta, Romit (New York [etc.] Routledge, 2013)
In Japan, the figure of the suited, white-collar office worker or business executive 'salaryman' (or, arariiman), came to be associated with Japan's economic transformation following World War Two. The ubiquitous salaryman came to signify both Japanese masculinity, and Japanese corporate culture, and in this sense, the salaryman embodied 'the archetypal citizen'.This book uses the figure of he salaryman to explore masculinity in Japan by examining the salaryman as a gendered construct. Whilst there is a considerable body of literature on Japanese corporate culture and a growing acknowledgement of the role of gender, until now the focus has been almost exclusively on women in the workplace. In contrast, this book is one of the first to focus on the men within Japanese corporate culture through a gendered lens. Not only does this add to the emerging literature on masculinity in Japan, but given the important role Japanese corporate culture has played in Japan's emergence as an industrial power, Romit Dasgupta's research offers a new way of looking both at Japanese business culture, and more generally at important changes in Japanese society in recent years.Based on intensive interviews carried out with young male private sector employees in Japan, this book makes an important contribution to the study of masculinity and Japanese corporate culture, in addition to providing an insight into Japanese culture more generally. As such it will be of great interest to students and scholars of Japanese studies, Japanese society and gender studies.
Keywords: Hombres -- Psicología; Corporativismo -- Japón